ANALYSIS OF CONSTRUCTION MANAGEMENT OF KINDERFIELD SCHOOL CIREBON DEVELOPMENT PROJECT - Dea Devira Hidayati; Saihul Anwar (Journal of Green Science and Technology, 2020)
Management of construction projects is becoming increasingly complex due to the many parties that interact in it and the increasingly high demands for quality of functions, comfort, security, aesthetics and sustainability. Therefore construction management is needed to ensure the efficiency and productivity of a construction project in meeting various expectations and requirements.  Contruction management analysis on this building project of Kinderfield School include volume measurment, RAB, cost recapitulation and working/occupation unit cost analysis, with use CPM method (Critical Path Method) is a method in identificating a stripe or working item critically. CPM method solves the problem with retreat and forward measurement.  From the weight measurment occupation based on Barchart analysis, Curva S and building PDM scedhule of Kinderfield School needs the times as long as 42 weeks with cost estimation Rp. 9,439,526,000,00..Keyword: Barchart, Construction Management, CPM (Critical Path Method), S-Curve.